I Know My Story and I Know Your Story: Developing a Conceptual Framework for Vicarious Life Stories. Issue 4 (30th April 2016) - Thomsen, Dorthe Kirkegaard; Pillemer, David B.
Abstract: Vicarious life stories are mental representations of other people's life stories. We propose a conceptual framework that situates the study of vicarious life stories at the crossroads between personality and social cognition, identifies their potential functions, and describes possible connections between vicarious and personal life stories. Two preliminary studies compared chapters and specific memories in personal and close others' life stories in two groups of student participants. Ages associated with chapters and specific memories in personal and vicarious life stories showed similar temporal distributions. Emotion ratings of both personal and vicarious life story chapters were related to personality traits and self‐esteem, although relations were more consistent for personal chapters. In conclusion, personal and vicarious life stories share important similarities. Mental models of other people include vicarious life stories that serve to expand the self as well as facilitate understanding of others.